2023
DOI: 10.14814/phy2.15608
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of extramitochondrial BCKDH and its uncoupling from AMP deaminase in type 2 diabetic OLETF rat hearts

Abstract: Systemic branched‐chain amino acid (BCAA) metabolism is dysregulated in cardiometabolic diseases. We previously demonstrated that upregulated AMP deaminase 3 (AMPD3) impairs cardiac energetics in a rat model of obese type 2 diabetes, Otsuka Long‐Evans‐Tokushima fatty (OLETF). Here, we hypothesized that the cardiac BCAA levels and the activity of branched‐chain α‐keto acid dehydrogenase (BCKDH), a rate‐limiting enzyme in BCAA metabolism, are altered by type 2 diabetes (T2DM), and that upregulated AMPD3 expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 62 publications
(122 reference statements)
0
4
0
Order By: Relevance
“…However, both have been comparatively understudied in the diabetic heart versus fatty acid and carbohydrate metabolism, while myocardial amino acid metabolism in general has been ignored. Nonetheless, it has been reported that branched chain α-ketoacid CoA dehydrogenase protein expression is decreased in hearts from genetically obese rats, suggestive of an impairment in myocardial branched chain amino acid metabolism ( 54 ).…”
Section: Cardiac Substrate Metabolism Perturbations In Dbcmmentioning
confidence: 99%
“…However, both have been comparatively understudied in the diabetic heart versus fatty acid and carbohydrate metabolism, while myocardial amino acid metabolism in general has been ignored. Nonetheless, it has been reported that branched chain α-ketoacid CoA dehydrogenase protein expression is decreased in hearts from genetically obese rats, suggestive of an impairment in myocardial branched chain amino acid metabolism ( 54 ).…”
Section: Cardiac Substrate Metabolism Perturbations In Dbcmmentioning
confidence: 99%
“…This portion of BCKDH is present on the endoplasmic reticulum (ER) and interacts with AMP deaminase 3 (AMPD3), and is negatively regulated by AMPD3. 72 Upregulation of AMPD3 has been reported to impair energy metabolism in OLETF hearts. This study further suggested that AMPD3 may induce cardiometabolic changes through AMPD3-BCKDH expression imbalance in cardiomyocytes of diabetic individuals, providing new insights into the mechanism of the development of this disease.…”
Section: Branched-chain Amino Acids (Bcaas)mentioning
confidence: 99%
“…This portion of BCKDH is present on the endoplasmic reticulum (ER) and interacts with AMP deaminase 3 (AMPD3), and is negatively regulated by AMPD3. 72 Upregulation of AMPD3 has Fig. 3 BCAAs metabolism in Cancer.…”
Section: Bcaas In Diseasementioning
confidence: 99%
See 1 more Smart Citation